Reliability and validity of body weight and body image perception in children and adolescents from the South American Youth/Child Cardiovascular and Environmental (SAYCARE) Study (2019)
ABSTRACT: Objective: To assess the reliability and validity of body weight (BW) and body image (BI) perception reported by parents (in children) and by adolescents in a South American population. Design: Cross-sectional study. BW perception was evaluated by the question, ‘Do you think you/your child are/is: severely wasted, wasted, normal weight, overweight, obese?’ BI perception was evaluated using the Gardner scale. To evaluate reliability, BW and BI perceptions were reported twice, two weeks apart. To evaluate validity, the BW and BI perceptions were compared with WHO BMI Z-scores. Kappa and Kendall’s tau-c coefficients were obtained. Setting: Public and private schools and high schools from six countries of South America (Argentina, Peru, Colombia, Uruguay, Chile, Brazil). Participants: Children aged 3–10 years (n 635) and adolescents aged 11–17 years (n 400). Results: Reliability of BW perception was fair in children’s parents (κ=0·337) and substantial in adolescents (κ=0·709). Validity of BW perception was slight in children’s parents (κ=0·176) and fair in adolescents (κ=0·268). When evaluating BI, most children were perceived by parents as having lower weight. Reliability of BI perception was slight in children’s parents (κ=0·124) and moderate in adolescents (κ=0·599). Validity of BI perception was poor in children’s parents (κ= − 0·018) and slight in adolescents (κ=0·023). Conclusions: Reliability of BW and BI perceptions was higher in adolescents tan in children’s parents. Validity of BW perception was good among the parents o the children and adolescents with underweight and normal weight.